Investigating the role of family members in postnatal care: Evidence from mother-caregiver dyads in India - Pooja Suri; Sahana SD; Shirley Yan; Seema Murthy; Jamie Sewan Johnston (PLoS ONE, 2025)
Objectives In this study, we examine the dynamics of birthing women relative to other family members in making caregiving decisions about postpartum maternal and infant care in four states in India. Specifically, we investigate the involvement of the father, maternal grandmother, and paternal grandmother of the newborn in household health decision-making. Methods We analyze data from 551 dyads of women with infants under six months and the family caregiver identified as providing the primary support in the postpartum period. We present descriptive statistics on 1) the identity of the primary decision-maker as independently reported by birthing women and caregivers and 2) how disagreements are resolved. Within each dyad, we examine the level of agreement on health decision-making between mothers and caregivers. We use regression models to analyze the association between caregiver identity, and postpartum outcomes. Results Our findings show that decisions in the household are predominantly made by a single person (around 70 percent), either the birthing woman or one of the caregivers – the father, maternal grandmother, or paternal grandmother of the newborn. Across all dyads, birthing women are more likely than other household members to name their caregivers as the sole decision-makers for infant care and their own. The involvement of birthing women in household decision-making is low, with less than a third of birthing women reporting involvement in either. Within-dyad agreement on the identity of sole decision-makers is low, with less than 30 percent of dyads in agreement for both infant and maternal care decision-making. Birthing women experience a higher level of mental well-being on a normalized index by 0.12 standard deviations (sd) when their primary caregiver is their own mother. In contrast, the mental well-being of the birthing women is negatively impacted by 0.10 sd when the caregiver is the mother-in-law. We also observe that the type of caregiver significantly impacts postpartum recovery of the birthing woman. Specifically, birthing women whose caregivers are mothers-in-law are 16.2 percentage points less likely to be well post-delivery. These findings enhance our understanding of the gendered role of caregivers in postnatal care in India, providing new insights into how caregiving and decision-making responsibilities are distributed within families.